Answer:
9
Step-by-step explanation:
17.91 divided by 1.99
Answer:
отлично вы молодец болшая у вас всё правилно
F(x) = 3x² - 1
f(-2) = 3(-2)² - 1
f(-2) = 3(4) - 1
f(-2) = 12 - 1
f(-2) = 11
f(x) = x < 1
f(-2) = -2 < 1
f(x) = x + 2
f(-2) = -2 + 2
f(-2) = 0
f(x) = x > 1
f(-2) = -2 > 1
f(-2) = -2 < 1
When you see the subtraction<span> (</span>minus<span>) sign followed by a </span>negative<span> sign, turn the two signs into a plus sign. Thus, instead of </span>subtracting<span> a </span>negative<span>, you're adding a </span>positive<span>, so you have a simple addition problem.</span>
Answer: 16, 18
Step-by-step explanation:
16 + 18 = 34